2017
DOI: 10.2147/cia.s138357
|View full text |Cite
|
Sign up to set email alerts
|

Aural stimulation with capsaicin ointment improved swallowing function in elderly patients with dysphagia: a randomized, placebo-controlled, double-blind, comparative study

Abstract: ObjectiveThe aim of this study was to assess whether aural stimulation with ointment containing capsaicin improves swallowing function in elderly patients with dysphagia.Study designA randomized, placebo-controlled, double-blind, comparative study.SettingsSecondary hospital.Patients and methodsTwenty elderly dysphagic patients with a history of cerebrovascular disorder or Parkinson’s disease were randomly divided into two groups: 10 receiving aural stimulation with 0.025% capsaicin ointment and 10 stimulated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 21 publications
0
31
1
Order By: Relevance
“…Recently, we have conducted a randomized placebo-controlled, double-blinded, comparative study regarding the aural stimulation with capsaicin ointment for dysphagia. The results showed that TRPV1-mediated stimulation of the external auditory canal with capsaicin improved glottal closure and cough reflexes in elderly patients with dysphagia, whereas non-specific mechanical aural stimulation with a cotton swab had no significant effect [9]. Therefore, the present findings suggest that the stimulation of TRPV1 on the Arnold's nerve of the external auditory canal with capsaicin ointment enhanced cough reflex to prevent pneumonia in the elderly dementia patients.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Recently, we have conducted a randomized placebo-controlled, double-blinded, comparative study regarding the aural stimulation with capsaicin ointment for dysphagia. The results showed that TRPV1-mediated stimulation of the external auditory canal with capsaicin improved glottal closure and cough reflexes in elderly patients with dysphagia, whereas non-specific mechanical aural stimulation with a cotton swab had no significant effect [9]. Therefore, the present findings suggest that the stimulation of TRPV1 on the Arnold's nerve of the external auditory canal with capsaicin ointment enhanced cough reflex to prevent pneumonia in the elderly dementia patients.…”
Section: Discussionmentioning
confidence: 53%
“…However, the oral administration with capsaicin pastille may increase a risk of aspiration conversely. In our previous study, we showed that the ectopic stimulation of the auricular branch of the vagus, the Arnold's nerve, with capsaicin ointment applied to the external auditory canal improves glottal closure and cough reflexes via the Arnold-cough reflex in elderly patients with dysphagia [8,9]. The findings suggest that daily aural stimulation with capsaicin ointment may prevent pneumonia in elderly at risk of aspiration.…”
mentioning
confidence: 99%
“…These hypotheses for the neural origin of kinematic differences between RLN and SLN lesioned pigs also suggest that different interventions may be effective to modify swallowing in each case. If the reduced sensitivity hypothesis is correct for explaining the patterns we see in the SLN lesioned animals, then either controlling bolus volume directly through regulated feeding, or increasing sensitivity of the valleculae by using other stimuli in conjunction with volume [i.e., capsaicin (31,32)] are likely to be most effective for restoring normal swallow function. In the case of RLN lesion, however, restoring something like normal function is likely to involve interventions that harness sensory motor mechanisms that establish coordination between tongue and pharyngeal components of swallowing, such as entrained milk delivery (28) or motor learning (33)(34)(35).…”
Section: Despite Both Resulting In Increased Aspiration Rln and Sln mentioning
confidence: 95%
“…Capsaicin can activate transient receptor potential in oropharyngeal sensory neurons, such as the pharynx branch of the glossopharyngeal nerve and the two branches of vagus nerve, the pharynx branch and the superior laryngeal nerve 42 . Capsaicin may promote the triggering of a swallowing response and may promote neuronal reorganisation 16 . Previous studies 43,44 have reported that the capsaicin can increase the concentration of substance P in saliva, increase the opening time of the neck oesophagus wall, shorten the swallowing reaction time and improve the safety and effectiveness of swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study 15 has reported that stimulation of transient receptor potential can be used as a target for the treatment of swallowing disorders, and the activation of transient receptor potential may improve the swallowing function. Capsaicin is an agonist of the transient receptor potential, which can activate peripheral C fibres and stimulate swallowing reflexes 16 . Previous study 17 has found that daily sensory stimulation with capsaicin can promote the remodelling of damaged nerves and improve swallowing function.…”
Section: Introductionmentioning
confidence: 99%